Análise da prevalência de sarcopenia, dinapenia e efeitos negativos dos índices de obesidade sobre a força muscular e qualidade muscular em pacientes renais crônicos - Bacci, Márcio Fernando (2024)
Dynapenia, sarcopenia and obesity are common comorbidities associated with chronic disease (CKD) and should be routinely screened for in clinical practice. This study aims to compare handgrip strength and muscle quality index of CKD patients, both male and female, with reference values for diagnosing dynapenia and sarcopenia, as well as evaluating the correlation between obesity, handgrip strength and muscle quality index. 78 individuals with CKD on maintenance hemodialysis participated in the study. Anthropometric analysis, body composition, handgrip strength, biomechanical analysis, functional performance test and muscle quality index assessments were made. Men had a significantly higher frequency of dynapenia (relative risk of 5.14 with a 95% CI of 2.28 – 11.60, higher than women) and sarcopenia (relative risk of 3.15 with a 95% CI of 1.88 – 5.30, higher than women), respectively than the women evaluated. Patients with CKD had lower handgrip strength (-5.72kg, p=0.001) and muscle quality index (-0.19, p=0.001) compared to reference values for diagnosing dynapenia and sarcopenia. Finally, obesity rates were negatively correlated with handgrip strength and muscle quality index. Men with CKD have muscle strength and muscle quality index values lower than the reference values proposed by EWGSOP2-2018 and FNIH. Futhermore, they demonstrate a higher relative risk for the diagnosis of dynapenia and sarcopenia when compared to women. Also high values in obesity rates negatively affect muscle strength and muscle quality in male and female CKD patients.